‘The meretricious charms of melody’? On Late Victorian Settings of the Nicene Creed - Rodmell, Paul (Journal of the Society for Musicology in Ireland, 2013)
In 1889 Frederick Harford, a canon of Westminster Abbey, and Charles Villiers Stanford, then one of the United Kingdom’s leading composers, entered into a fractious argument in the pages of The Musical World regarding the manner in which the Nicene Creed should be set to music for use in Anglican communion services. This article sets out the terms of this argument by examining Harford’s proposed guidance, initially directed at aspiring composers of church music, which covered matters of doctrine, syntax, and verbal accentuation. The responses of Stanford and other correspondents are then scrutinized, as is the fallout from the episode, which included the widespread canvassing of eminent clergymen on the niceties of Harford’s argument, and a competition for new settings, organized by The Musical World. This is followed by an examination of Stanford’s own settings of the Creed, most particularly those in B flat, Op. 10, and in F, Op. 36, and the responses to Harford’s guidance that can be seen in contemporaneous settings of the text by other composers. The intricate aspects of this debate are put into the wider context of the changing status of music and musicians, and evolving liturgical practices and attitudes to the employment of music, in the Anglican Church of the Victorian era.